The effect of digital leadership and organizational support on innovative work behavior: the mediating role of emotional intelligence - Syamsul Hadi; Lina Setiawati; Kusuma Chandra Kirana; Suddin Lada; Christina Heti Tri Rahmawati (Elsevier B.V., 2024)
The purpose of this research is to analyze the effect of digital leadership and organizational support on innovative work behavior mediated by emotional intelligence. The implementation of a management pattern from conventional to digital era requires adaptation and transition from old to new habits that must be adhered to by all human resources. This frequently causes discomfort, anxiety, and fear to the detriment of employees' self-confidence due to the inability to keep up with the technology acceleration. Methodology, The population of this study was all lecturers of the Faculty of Fine Arts, Institut Seni Indonesia (ISI) Yogyakarta, the sampling technique used was a saturated sample of 119 lecturers through a questionnaire, and the data analysis tool used was SmartPLS version 3.2.9 software. Research results show that digital leadership is not proved to have a positive influence on innovative work behavior, organizational support has a positive and significant effect on innovative work behavior, digital leadership is not proved to have a positive effect on lecturers' emotional intelligence, organizational support has a positive and significant effect on lecturers’ emotional intelligence, and emotional intelligence has a positive and significant effect on lecturers' innovative work behavior. Future research is expected to be able to build a comparative analysis study by comparing two material objects, which are two institutions/universities with state and private status and it is recommended to use mixed methods, namely quantitative and qualitative approaches through deep review and add variables that influence innovative work behavior, namely efficiency variables. Thus, the study will obtain better research results.